Diet composition of two hylid species (Dendropsophus haraldschultzi and D. minutus) in anthropogenic environments in eastern Amazonia - Sangel Soeiro, Ana Luiza (2022)
The diet composition of hylids ranges from generalist to specialist, depending on the relative proportions of different types of prey found in their gastrointestinal tracts and trophic niche. Here, we report the diet composition and compare the niche breadth of two syntopic hylid species in eastern Amazonia, Dendropsophus haraldschultzi and D. minutus, which use anthropogenic environments during the rainy season. We collected 32 individuals of D. haraldschultzi and 30 individuals of D. minutus. The most important preys found in the diet of D. haraldschultzi were Hemiptera (34.6%), whereas Lepidoptera larvae (63.8%) were predominant in the diet of D. minutus. Both Dendropsophus species had a similar niche breadth with generalist characteristics. The consumption of mobile and slow-moving prey, and hard-bodied and soft-bodied arthropods, indicated a combined use of both “sit-and-wait” and “active search” foraging strategies.